The Caring Life Course Theory: Opening new frontiers in care—A cardiac rehabilitation example - Pinero de Plaza, Maria Alejandra; Hutchinson, Claire; Beleigoli, Alline; Tieu, Matthew; Lawless, Michael; Conroy, Tiffany; Feo, Rebecca; Clark, Robyn A.; Dafny, Hila; McMillan, Penelope; Allande‐Cussó, Regina; Kitson, Alison A. (Journal of advanced nursing, 2025)
Aim(s) To operationalize the Caring Life Course Theory (CLCT) as a framework for improving cardiac rehabilitation (CR) engagement and informing ways to address disparities in rural, low socio‐economic areas. Methods A secondary analysis of data collected from 15 CR programmes to identify CR patterns through the CLCT lens using a mixed‐methods approach. All analytical processes were conducted in NVivo, coding qualitative data through thematic analysis based on CLCT constructs. Relationships among these constructs were quantitatively assessed using Jaccard coefficients and hierarchical clustering via dendrogram analysis to identify related clusters. Results A strong interconnectedness among constructs: ‘care from others’, ‘capability’, ‘care network’ and ‘care provision’ (coefficient = 1) highlights their entangled crucial role in CR. However, significant conceptual disparities between ‘care biography’ and ‘fundamental care’ (coefficient = 0.4) and between ‘self‐care’ and ‘care biography’ (coefficient = 0.384615) indicate a need for more aligned and personalized care approaches within CR. Conclusion The CLCT provides a comprehensive theoretical and practical framework to address disparities in CR, facilitating a personalized approach to enhance engagement in rural and underserved regions. Implications Integrating CLCT into CR programme designs could effectively address participation challenges, demonstrating the theory's utility in developing targeted, accessible care interventions/solutions. Impact Explored the challenge of low CR engagement in rural, low socio‐economic settings. Uncovered care provision, transitions and individual care biographies' relevance for CR engagement. Demonstrated the potential of CLCT to inform/transform CR services for underserved populations, impacting practices and outcomes. Reporting Method EQUATOR—MMR‐RHS. Patient Contribution A consumer co‐researcher contributed to all study phases.